2007
DOI: 10.1111/j.1872-034x.2007.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum biotinidase is a sensitive and specific biochemical marker of hepatic dysfunction: A preliminary report

Abstract: Biotinidase is an enzyme synthesized predominantly by the liver. Serum activity of this enzyme has been shown to be low in chronic liver disease. In this study, we endeavored to assess the diagnostic value of serum biotinidase as a marker of hepatic biosynthetic function in acute and chronic liver dysfunction. Twenty-three patients with acute liver disease and 46 with chronic liver disease, as diagnosed by clinical examination, laboratory tests, histopathology and tests for viral markers, were inducted into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Similarly, Grier et al found low serum biotinidase activities in patients with chronic liver disease (10). Meanwhile, Faith et al in their preliminary report suggested that serum biotinidase might be a sensitive and specific diagnostic marker of hepatic biosynthetic function in both acute and chronic liver disease (12). Meanwhile, Faith et al in their preliminary report suggested that serum biotinidase might be a sensitive and specific diagnostic marker of hepatic biosynthetic function in both acute and chronic liver disease (12).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Grier et al found low serum biotinidase activities in patients with chronic liver disease (10). Meanwhile, Faith et al in their preliminary report suggested that serum biotinidase might be a sensitive and specific diagnostic marker of hepatic biosynthetic function in both acute and chronic liver disease (12). Meanwhile, Faith et al in their preliminary report suggested that serum biotinidase might be a sensitive and specific diagnostic marker of hepatic biosynthetic function in both acute and chronic liver disease (12).…”
Section: Discussionmentioning
confidence: 99%
“…Then the analyses of those samples are usually carried out using the same method for comparison. Most of the possible biomarkers being proposed and under study are biomolecules such as proteins and enzymes [6–9]. Analysis of biomarkers in samples with complicated matrices like body fluids requires highly specific and sensitive techniques.…”
Section: Introductionmentioning
confidence: 99%